Pain situations among working adults and the educational needs identified: an exploratory survey via WeChat - Yajie Li (BMC Public Health, 2019)
Abstract Objectives The aim of this study is to 1) investigate the pain situation among working adults in China; 2) explore the self-initiate pain reliving strategies applied by working adults; and 3) collect people’s interests and suggestions to the topics of the online pain education program. Methods This is an exploratory survey through WeChat. The study was conducted from May 2018 to December 2018. Participants were recruited following the snowball sampling. In total of 664 people were recruited and 502 satisfied the criteria. SPSS was used for data analysis. Descriptive statistical analysis were used to present the utilization of pain treatments and suggested topics. Chi-square test, independent multiple logistic regression and Spearman’s correlation were used to analysis the data. Results The overall incidence of pain among the participants is 45% and higher among female (63%) than male (37%). Neck (68.72%, 4.10 ± 2.31), shoulder (62.56%, 3.78 ± 2.41) and head (49.34%, 4.23 ± 2.52) are reported as the most common and severe pain sites. Working is affected by pain and the results show that there is a negative correlation between pain intensity and work (rs = − 0.194) among the working population. Non-pharmacological treatments (55.77%) were chosen more by pain suffers. Totally 63.39% of participants show interests in the online pain education program and physical and psychological impact of pain is the most suggested topic (22.51%). Conclusion The pain prevalence is high among working adults in China. Impact of pain on work is a significant problem for the working adults. It is important to identify people at risk and deliver timely intervention to reduce pain. People showed their willingness in joining the online program. Therefore, future online pain education program can be developed.